Interlanguage Pragmatic Motivation in EFL Context - Widya Caterine Perdhani (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This research sets out to explore the Interlanguage pragmatic motivation in EFL to their pragmatic production. This research is focus on the construct and impact of Interlanguage pragmatic motivation in EFL to their pragmatic production. The participants of the study were the university students chosen randomly from among intermediate EFL learners. There are three instruments in this study; there will be different types of analyses. Both general and speech-act-specific motivation questionnaires will be analysed by using factor analysis on a five-point Likert scale (1-5). Skewness and kurtosis will be calculated to investigate whether the questionnaires and the WDCT items fell within the normal range. Regression analysis will be done to measure how well general pragmatic motivation and Speech-act-specific motivation could predict pragmatic production. Several conclusions can be drawn from the resent study. First, language learners possess a specific type of motivation for the acquisition of interlanguage pragmatics, called pragmatic motivation, which refers to two interrelated types of motivation: general pragmatic motivation and speech-act-specific motivation. Second, EFL learners are strongly motivated to acquire and develop English pragmatic features, i.e. their pragmatic motivation is high; however, they do not have the necessary pragmatic knowledge. Third, predicting EFL learners’ pragmatic production based on their speech-act-specific motivation is somehow possible since both pragmatic production and speech-act-specific motivation focus on learners’ illocutionary competence, i.e. language functions and speech acts.